2019
DOI: 10.14712/18047106.1320
|View full text |Cite
|
Sign up to set email alerts
|

Hodnotenie v prírodovedných predmetoch v podmienkach slovenského školstva

Abstract: Hodnotenie má výrazný vplyv na osobnosť žiaka, na proces jeho učenia sa a v konečnom dôsledku i na vytváranie jeho vzťahu k obsahu vyučovacieho predmetu. Národná správa PISA 2015 (NÚCEM, 2017) poukazuje na pokles výkonu žiakov v prírodovednej gramotnosti, pričom najväčšou rizikovou skupinou žiakov sú práve žiaci základných škôl a stredných odborných škôl bez maturity. Pred pedagógmi tak stojí otázka, ako tento stav pozitívne ovplyvniť. Jednou z možností sa javí, na základe mnohých výskumov, formatívne hodnoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Afterward, the enhancement of formative assessment was related to the introduction of inquiry-based methods , and the realization of the two European FP7 projects: ESTABLISH (2010–2014) and SAILS (2012–2015) . Currently, there are several national projects that focus on the implementation of formative assessment in various school subjects, and this topic is spread across the country. , Orosová et al studied the status of assessment in Slovak schools in STEM. She concluded that teachers prefer using summative assessment over formative assessment.…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, the enhancement of formative assessment was related to the introduction of inquiry-based methods , and the realization of the two European FP7 projects: ESTABLISH (2010–2014) and SAILS (2012–2015) . Currently, there are several national projects that focus on the implementation of formative assessment in various school subjects, and this topic is spread across the country. , Orosová et al studied the status of assessment in Slovak schools in STEM. She concluded that teachers prefer using summative assessment over formative assessment.…”
Section: Research Backgroundmentioning
confidence: 99%
“…59 Currently, there are several national projects that focus on the implementation of formative assessment in various school subjects, and this topic is spread across the country. 6 , 60 63 Orosová et al 64 studied the status of assessment in Slovak schools in STEM. She concluded that teachers prefer using summative assessment over formative assessment.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The research shows that teachers in practice have heard of the terms: assessment for learning, assessment as learning, assessment of learning, but do not know and cannot explain their meaning (Szarka, Brestenská & Ganajová, 2019), the research is also based on the fact that the interest in tools of formative assessment by teachers is low (Orosová, Ganajová, Szarka & Babinčáková, 2019, Matějka & Miština, 2022 It is possible to eliminate this situation in relation to teachers by preparing practical training for teachers to develop assessment literacy, emphasis on formative assessment in their subject and implementation of formative assessment in undergraduate preparation of students of pedagogical faculties.…”
Section: Training Of Future Teachers In the Field Of Class-hour Asses...mentioning
confidence: 99%
“…The OECD evaluation team has brought attention to the need to improve students' understanding by using formative assessment (Shewbridge et al, 2014). This situation has also been addressed by Orosová et al (2019) and Ganajová et al (2019). Their research has shown that Slovak teachers use summative assessment more frequently than formative assessment as some of them are not familiar with formative assessment and they do not understand its methods or aim.…”
Section: Introductionmentioning
confidence: 99%